THE EFFECTS OF LEVERAGE, OPERATING CAPACITY AND PROFITABILITY ON FINANCIAL DISTRESS IN TRANSPORTATION COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE FOR THE PERIOD 2018-2022 - Iqbal, Muhammad; Cholifah, Amalia Nur (Jurnal Akuntansi Syariah (JAkSya), 2025)
This research seeks to examine how leverage, operating capacity, and profitability impact financial distress. The study uses quantitative data sourced from secondary data. The population targeted includes transportation companies listed on the Indonesia Stock Exchange from 2018 to 2022, all of which have audited annual reports. The analysis method used is multiple linier regression, with purposive sampling as the sampling technique, resulting in a total of 40 companies experiencing financial distress. Results indicate that leverage has a significant negative impact on financial distress during the specified period. Meanwhile, operating capacity significantly and positively affects financial distress, whereas profitability does not show a significant impact on financial distress in transportation companies listed on the Indonesia Stock Exchange for the period 2018-2022